Wrongful convictions: an analysis of laws and cases in Malaysia and selected jurisdictions in the United States / Nur Atiqah Syazana Mohd Nasir … [et al.] - Mohd Nasir, Nur Atiqah Syazana; Abdul Halim, Diyana; Salleh, Liyana Amira; Azmi, Amir 'Arif (2013)
Wrongful conviction is a serious problem in any jurisdiction including Malaysia. There are many causes of wrongful convictions such as false or coerced compliant confessions, erroneous eyewitness identification and testimony, overzealous law enforcement officers, prosecutorial misconduct, false confessions, mass media coverage, over-reliance on in-custody informants, and unsound forensic science or its misuse. However, the two most prominent causes of wrongful convictions are false confessions and misapplication of forensic evidence. Wrongful convictions will also affect the wrongfully convicted psychologically, physically and financially. Compensation laws for the wrongfully convicted must be introduced in Malaysia since there are no such laws available in the country and there is also a fundamental need for the causes of wrongful conviction to be remedied.